ASSESSMENT OF ENGLISH AS A SECOND LANGUAGE - Uzganova Gulhayo Faxritdin qizi; Otaboyev Muzaffar (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Assessment of English proficiency is essential for individuals learning English as a second language (ESL). It provides valuable insights into learners' language skills and facilitates their academic and professional advancement. This article delves into the various methods and tools used to assess ESL proficiency, examining their effectiveness and validity.